Anthropogenic trauma is the most prevalent cause of mortality in Little Penguins, Eudyptula minor, in Perth, Western Australia. (1st March 2016) - Cannell, B. L.; Campbell, K.; Fitzgerald, L.; Lewis, J. A.; Baran, I. J.; Stephens, N. S.
Abstract: Penguins both forage and travel in the marine environment and so spend a much greater proportion of their lives in this environment than other seabirds. This maximises their exposure to an increasing range of threats compared with other seabirds. From late 2003 to 2012, necropsies were performed on 159 Little Penguins found in the Perth region, Western Australia. Given the close proximity of the colonies to increasingly populated urban areas, the aims of this study were to: (1) determine the causes of mortality; (2) determine the proportion of deaths attributable to anthropogenic causes; (3) use this information to help guide management strategies; and (4) identify potential threats to coastal seabirds in general. In most cases, cause of mortality could be assigned to one of 11 categories. Trauma, most likely from watercraft, was the main cause of mortality. The next most common cause, starvation, was more likely to occur in spring and summer. Management strategies for colonies of Little Penguins near high levels of watercraft activity should take into account the risk of injury or death from watercraft strikes.